2021
DOI: 10.1017/jmo.2021.13
|View full text |Cite
|
Sign up to set email alerts
|

Work–family conflict and job performance: mediating role of work engagement in healthcare employees

Abstract: This study aims to examine the mediating role of work engagement in the effect of work interfering with the family (WIF) and family interfering with the work (FIW) on employees' employee-rated and supervisor-rated contextual and task performance, drawing on Job Demands and Job Resources model. The sample of the study consisted of 432 healthcare employees and 61 supervisors working for public hospitals in Turkey. We found support for a mediational model such that the relationship between FIW and employee-rated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 77 publications
0
7
0
5
Order By: Relevance
“…These work-related factors can easily lead to work–family conflict [ 15 ]. Miners’ time with their families is further reduced, which makes them even less able to shoulder their family responsibilities during the COVID-19 pandemic [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These work-related factors can easily lead to work–family conflict [ 15 ]. Miners’ time with their families is further reduced, which makes them even less able to shoulder their family responsibilities during the COVID-19 pandemic [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, employees with high work engagement have a strong work identity and expect to achieve good results such as high performance through work [ 34 ]. Indeed, several studies have shown that work engagement is positively related to job performance [ 35 , 36 , 37 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Estos resultados apuntan a los de Ibarra-Cisneros & Hernández-Perlines (2019) quienes mencionan que el CH y el desempeño no presentan asociación alguna, en cambio Reyes (2018) manifiesta que las organizaciones ponen total énfasis en el CH y lo enriquecen con mejorar sus habilidades de trabajo en equipo. Sin embargo, la literatura evidencia que la educación y la experiencia afectan el desempeño laboral (Huang et al, 2021), este último pueden estar mediado por el compromiso afectivo y el capital humano (Harini et al, 2020), por lo tanto el compromiso laboral media a la familia que interfiere en el trabajo y el desempeño contextual (Şahin & Yozgat, 2021). Cabe precisar que el equilibrio entre el trabajo y la vida personal y los conflictos entre el trabajo y la familia influyen de manera positiva en el desempeño (Soomro et al, 2018), en cambio, el conflicto entre el trabajo y la familia tiene un efecto positivo en el desempeño creativo sostenible a través de la elaboración del trabajo, y el efecto es más fuerte cuando el capital humano muestra mayor enfoque regulatorio de promoción (Zhang et al, 2020).…”
Section: Modelosunclassified
“…El agotamiento emocional, la sobrecarga del trabajo, cansancio físico, estado de ánimo y estrés laboral son factores causales en la reducción en el desempeño laboral y puede ser moderada por el apoyo social por parte de la institución como de la familia (An et al, 2020;Ismail & Gali, 2017;Yang et al, 2021;Zainal et al, 2020), en cambio la existencia y accesibilidad de las políticas trabajo-familia relativas a flexibilidad temporal, permisos largos y el lugar de trabajo no influyen en la mejora del desempeño, pero sí a través del bienestar laboral (Medina-Garrido et al, 2017), además de poder estar mediada por el compromiso laboral, seguridad y el bienestar psicológicos (Obrenovic et al, 2020;Şahin & Yozgat, 2021). Por su parte, Wang et al, (2021), encontraron que el cuidado de la organización reduce los efectos negativos del conflicto familia-trabajo en el desempeño laboral, además de que la interferencia familiar laboral se correlaciona negativamente con el desempeño laboral y es moderada por el apoyo social recibido de los supervisores y miembros de la familia (Zainal et al, 2020).…”
Section: Modelosunclassified
See 1 more Smart Citation